Pele ramseyi, a new genus and new species of anchialine swimming crab (Crustacea: Brachyura: Portunidae) from the Hawaiian Islands - Ng, Peter K. L. (Zootaxa, 2011)
A new genus and new species of anchialine portunid crab is described from lava pools in Maui, Hawaiian Islands. Pele ramseyi new genus, new species, resembles species of Libystes A. Milne-Edwards, 1867, but differs markedly in its reduced and almost immovable eyes, as well as the distinctive structures of the mouthparts, chelipeds, male abdomen and gonopods.